An optimized method for obtaining clinical‐grade specific cell subpopulations from human umbilical cord‐derived mesenchymal stem cells. Issue 10 (29th June 2022) - Jia, Yali; Wang, Ailin; Zhao, Bichun; Wang, Chao; Su, Ruyu; Zhang, Biao; Fan, Zeng; Zeng, Quan; He, Lijuan; Pei, Xuetao; Yue, Wen
Abstract: Mesenchymal stem cells (MSCs) are heterogeneous populations with broad application prospects in cell therapy, and using specific subpopulations of MSCs can enhance their particular capability under certain conditions and achieve better therapeutic effects. However, no studies have reported how to obtain high‐quality specific MSC subpopulations in vitro culture. Here, for the first time, we established a general operation process for obtaining high‐quality clinical‐grade cell subpopulations from human umbilical cord MSCs (hUC‐MSCs) based on particular markers. We used the MSC‐CD106 + subpopulations, whose biological function has been well documented, as an example to explore and optimize the crucial links of primary preparation, pre‐treatment, antibody incubation, flow sorting, quality and function test. After comprehensively evaluating the quality and function of the acquired MSC‐CD106 + subpopulations, including in vitro cell viability, apoptosis, proliferation, marker stability, adhesion ability, migration ability, tubule formation ability, immunomodulatory function and in vivo wound healing ability and proangiogenic activity, we defined an important pre‐treatment scheme which might effectively improve the therapeutic efficiency of MSC‐CD106 + subpopulations in two critical clinical application scenarios—direct injection after cell sorting and post‐culture injection into bodies. Based on the above, we tried to establish a general five‐step operation procedure for acquiring high‐quality clinical‐grade MSC subpopulations based on specific markers, which cannot only improve their enrichment efficiency and the reliability of preclinical studies, but also provide valuable methodological guidance for the rapid clinical transformation of specific MSC subpopulations. Abstract : We established an optimized operation process for obtaining human umbilical cord mesenchymal stem cells (hUC‐MSC) subpopulations with specific markers, which is also suitable for MSCs derived from other tissues. Step One . Preparation of clinical‐grade hUC‐MSCs. The clinical‐grade hUC‐MSCs obtained fully comply with the cGMP guidelines and meet the quality standards of the NIFDC. Step Two . Removal of non‐specific sites and poor‐quality cells without cellular damage. Treatment with MACS was proved as a safe and effective pre‐treatment by verifying multiple core indicators related to subpopulation quality. Step Three . Incubation with the antibodies against specific functional markers. Select the optimum condition of specific antibodies to ensure the purity of subsets obtained by subsequent sorting. Step Four . Flow Sorting and obtaining hUC‐MSC subpopulations with specific markers. This step has higher technical requirements related to flow cytometry. Step Five . Quality test and function research of hUC‐MSC subpopulations with specific markers. Do more research and verification to ensure the efficiency of clinical transformation of the obtained MSC subpopulations. Application Scenes . The clinical‐grade MSC subpopulations obtained through the above‐optimized operation process do not only guarantee the quality of the cells in basic research and preclinical research but also provide safety assurance for clinical application.